Nephroblastoma Arising from Primary Testicular Germ Cell Tumor: A Case Report and Literature Review. (10th November 2016) - Alatassi, Houda; O'Bryan, Brittany E.; Messer, Jamie C.; Wang, Zhenglong
Abstract : Adult extrarenal nephroblastoma is a very rare tumor. Nephroblastoma arising from primary testicular germ cell tumor is exceedingly rare. To our knowledge, only three cases have been reported in the English literature. We report a case of a 19-year-old man who presented with a large right testicle. Image studies showed a large retroperitoneal mass along with liver and lung metastases. Orchiectomy demonstrated a mixed germ cell tumor composed of yolk sac tumor, embryonal carcinoma, and mature and immature teratoma with a significant portion of nephroblastoma. The patient received chemotherapy and no recurrence was noted during six months of followup. WT-1 expression was also studied due to the lack of consistency of its expression in testicular nephroblastoma in the literature. We also present a discussion and review of the literature due to its rarity, which indicate an adverse prognosis for patients with nephroblastoma components receiving standard chemotherapeutical regimes for testicular germ cell tumors.